The Role of Accounting Information Systems on the Quality of Financial Reports of the West Aceh District Land Office - Said, M Ikbal; Mahdani, Said (Cattleya Darmaya Fortuna, 2023)
The purpose of this study was to determine the role of the accounting information system on the quality of the financial reports of the West Aceh District Land Office. This study uses a quantitative descriptive method. The population in this study were 15 employees of the West Aceh District Land Office who were taken by purposive sampling. This study uses primary data collected from questionnaires distributed to employees of the West Aceh District Land Office. The variables used consist of AIS (X) and the quality of financial reports, (Y). Then the data collected is analyzed using a method that is testing the coefficient of determination. The results of this study are that the role of SIA does not have a major impact on the quality of the financial reports of the West Aceh District Land Office.